A R2R3-MYB transcription factor VvMYBF1 from grapevine (Vitis vinifera L.) regulates flavonoids accumulation and abiotic stress tolerance in transgenic Arabidopsis. Issue 2 (3rd March 2020) - Wang, Jizhong; Wang, Feibing; Jin, Cong; Tong, Yao; Wang, Tian
ABSTRACT: Transcriptional regulation is the most important tool for enhancing flavonoid biosynthesis of plants. The grapevine VvMYBF1 gene has been shown to be involved in the regulation of flavonoid biosynthesis. However, very little is known about its roles in tolerance to abiotic stresses. In this study, VvMYBF1 gene was cloned from grapevine. Its overexpression significantly increased accumulation of flavonoids and salt and drought tolerance in transgenic Arabidopsis . Real-time quantitative PCR analysis showed that overexpression of VvMYBF1 up-regulated the genes related to flavonoid and proline biosynthesis, stress responses and ROS scavenging under salt and drought stresses. Further components analyses showed that the transgenic plants exhibited significant increases of total flavonoids and proline content, as well as significant reduction of H2O2 and malonaldehyde (MDA) content. Enzymatic analyses found that the significant increases of phenylalanine ammonia lyase (PAL), chalcone isomerase (CHI), flavonol synthase (FLS), dihydroflavonol reductase (DFR), pyrroline-5-carboxylate synthase (P5CS), superoxide dismutase (SOD) and peroxidase (POD) activities were observed in the transgenic plants. These findings imply functions of VvMYBF1 in accumulation of flavonoids and tolerance to salt and drought stresses. The VvMYBF1 gene has the potential to be used to increase the content of valuable flavonoids and improve tolerance to abiotic stresses in plants.